If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying rx + -1s = 0 Solving rx + -1s = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add 's' to each side of the equation. rx + -1s + s = 0 + s Combine like terms: -1s + s = 0 rx + 0 = 0 + s rx = 0 + s Remove the zero: rx = s Divide each side by 'x'. r = sx-1 Simplifying r = sx-1
| 112-42x=32x+16 | | 64-s=25 | | 11x-5x+6=-24-9x | | 7p+4p+13=9 | | b-44=6 | | cy-d=4 | | 7.8y+2=165.8 | | z-13=13 | | t+52=61 | | 2(x+5)+x=34 | | 11x=385 | | x-c=d | | p+7=111 | | 7(x-60)=5180 | | 15p+3p^2=20 | | x-2=r | | 9x^2+30x=10(3x+5)-25 | | 6=15m | | 2(x+x+20)=84 | | 8-7x=73-42x | | n+63=108 | | 6x-5=5x+59 | | x-16=-8 | | 3r+10=34 | | 36=3(2-4x) | | x+(-150)=90 | | 2x+9=x+1 | | 9x*2+30x=10(3x+5)-25 | | 12-2y=5 | | e-28=44 | | 4(x-10)=-6(2-x)+6 | | 60=-15z |